DOI: 10.18297/etd/2693
|View full text |Cite
|
Sign up to set email alerts
|

Peeking into the other half of the glass : handling polarization in recommender systems.

Abstract: This dissertation is about filtering and discovering information online while using recommender systems. In the first part of our research, we study the phenomenon of polarization and its impact on filtering and discovering information. Polarization is a social phenomenon, with serious consequences, in real-life, particularly on social media. Thus it is important to understand how machine learning algorithms, especially recommender systems, behave in polarized environments. We study polarization within the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…Similar to our observations, they showed that predicting ratings for controversial items is much worse than for other items. Badami surveyed state-of-the-art research on the polarization [2], finding that many trust-based RS attempts to improve recommendation for controversial items by defining a trusted network for each user, e.g., [11,27,30,35]. Recently, Beutel et al proposed a focused learning model to improve the recommendation quality for a specified subset of items, through hyper-parameter optimization and a customized matrix factorization objective [4].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to our observations, they showed that predicting ratings for controversial items is much worse than for other items. Badami surveyed state-of-the-art research on the polarization [2], finding that many trust-based RS attempts to improve recommendation for controversial items by defining a trusted network for each user, e.g., [11,27,30,35]. Recently, Beutel et al proposed a focused learning model to improve the recommendation quality for a specified subset of items, through hyper-parameter optimization and a customized matrix factorization objective [4].…”
Section: Related Workmentioning
confidence: 99%
“…While the importance of the distribution of ratings on RS has been long recognized, e.g., [1,2,15,36], many popular methods based on latent factor models and recently introduced neural variants [3,14,20,22,25,39] optimize for the head of these distributions, potentially leading to large estimation errors for tail ratings. As we will show in Section 3, these tail estimation errors are common across multiple domains and datasets, leading to large overestimations of the ratings of items with very low ratings, and large under-estimations of the ratings of items with very high ratings.…”
mentioning
confidence: 99%
“…Our interactions with recommender systems naturally generate new data which is then used to update or retrain the next iteration of recommender system models, thus effectively creating a closed feedback loop [25,28] that affects the stream of information visible to us, and consequently, our capacity to discover information online. Possible impacts of limited discovery include the creation of filter bubbles and polarization [6][7][8]. Previous research has focused on dealing with this problem by aiming at increasing the diversity of the recommendation through several post-processing and preprocessing techniques [10,36] .…”
Section: Introductionmentioning
confidence: 99%
“…This recent work has shown that negative links have significant added value over positive links for various analytical tasks. For example, a small number of negative links improves the performance of recommender systems in arXiv:1804.07210v4 [cs.SI] 16 Aug 2018 social media [4][5][6][7][8]. Similarly, trust and distrust relations in Epinions can help users find high-quality and reliable reviews [9].…”
Section: Introductionmentioning
confidence: 99%
“…social media [4][5][6][7][8]. Similarly, trust and distrust relations in Epinions can help users find high-quality and reliable reviews [9].…”
Section: Introductionmentioning
confidence: 99%